Nontargeted metabolomic analysis of skeletal muscle in a dehydroepiandrosterone‐induced mouse model of polycystic ovary syndrome. Issue 4 (22nd January 2019) - Shen, Qiyang; Bi, Hai; Yu, Fuhai; Fan, Liting; Zhu, Menliang; Jia, Xiao; Kang, Jihong
Abstract : Polycystic ovary syndrome (PCOS) is the most common endocrinopathy and an important metabolic disorder in women of reproductive age. Insulin resistance (IR) is one of its most important clinical features in patients with PCOS. Androgen excess‐induced mitochondrial dysfunction contributes to skeletal muscle IR in dehydroepiandrosterone (DHEA)‐induced PCOS mice. The effect of androgen excess on the skeletal muscle, however, is incompletely characterized. A nontargeted metabolomics approach was thus applied to analyze the metabolites in skeletal muscle of DHEA‐induced PCOS mice. Data from metabolomic analysis revealed the significant changes in 32 metabolites and the marked impact of five metabolic pathways. ATP production was also found to be significantly reduced in skeletal muscle of DHEA mice. Combined with the quantification of type I and II myofibers and lipid measurement in the skeletal muscle of the mice, the results from the present study supported the role of mitochondrial impairment rather than lipid accumulation in the pathogenesis of skeletal muscle IR in DHEA‐induced PCOS mice. In summary, we show here for the first time the profile of the metabolites in the skeletal muscle of DHEA‐induced PCOS mice which exhibit IR. The work would help better understand the pathology of skeletal muscle IR in PCOS.